PENGARUH KOMPETENSI PROFESIONAL DAN EFIKASI GURU TERHADAP PENGELOLAAN KELAS DIMODERASI BUDAYA ORGANISASIONAL (Studi pada Guru SMP Negeri Sub Rayon 03 Kota Semarang) - Purnomowati, Heni; Fauzan, Mohammad (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to analyze the effect of professional competence and teacher efficacy on class management in moderation of organizational culture. The population in this study is the teacher of SMP Negeri Sub Rayon 03 Kota Semarang as much as 289 people, and the sample taken 150 teachers as respondents. Methods of data collection using questionnaire, while the analysis technique used regression with SPSS program.The result of analysis shows: 1. The professional competence has positive effect on class management 2. The teacher efficacy has positive effect on class management 3. That organizational culture has positive effect on class management 4. The organizational culture can not moderate the effect of professional competence on class management 5. The organizational culture can strengthen the effect of teacher efficacy on class management in SMP Negeri Sub Rayon 03 Kota Semarang. Keywords: professional competence, teacher efficacy, organizational culture, class management.